LARGE CLASSES IN SOCIAL WORK EDUCATION: A THREAT TO THE PROFESSIONAL SOCIALISATION OF SOCIAL WORK STUDENTS? - Simpson, Barbara (Social Work/Maatskaplike Werk, 2015)
Improved access to higher education and the increase in student numbers without a simultaneous increase in resources has given rise to numerous challenges. This reflective article considers whether large classes in social work education pose a threat to the professional socialisation of students, which requires that they internalise the values, interests, skills and knowledge of social work. Professional socialisation within social work education, the threat posed by large classes, both in the classroom and field practice education, as well as some possible solutions, are considered in this article.